2009
DOI: 10.1152/ajprenal.00164.2009
|View full text |Cite
|
Sign up to set email alerts
|

The full-length calcium-sensing receptor dampens the calcemic response to 1α,25(OH)2 vitamin D3 in vivo independently of parathyroid hormone

Abstract: 1Alpha,25(OH)(2) vitamin D(3) [1,25(OH)(2)D(3)] increases serum Ca(2+) concentration in vivo, an action counteracted by activation of the Ca(2+)-sensing receptor (CaSR), which decreases parathyroid hormone (PTH) secretion and increases renal Ca(2+) excretion. Relatively little is known of the role the CaSR plays in this response through its potentially direct actions in kidney, gut, and bone independently of PTH. We report PTH-independent roles of the CaSR in modulating the response to exogenous 1,25(OH)(2)D(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…We then treated TPTX, PTH-supplemented rats with an antibone-resorptive agent (2.5 μg pamidronate.g BW -1 , daily for 4 days prior to the experiment); this treatment significantly inhibits bone resorption in rats and mice as validated in previous studies (9,12,13). As shown in Figure 4, at baseline, both groups of rats exhibited the same blood ionized Ca concentration and urinary Ca excretion.…”
Section: Figurementioning
confidence: 67%
See 2 more Smart Citations
“…We then treated TPTX, PTH-supplemented rats with an antibone-resorptive agent (2.5 μg pamidronate.g BW -1 , daily for 4 days prior to the experiment); this treatment significantly inhibits bone resorption in rats and mice as validated in previous studies (9,12,13). As shown in Figure 4, at baseline, both groups of rats exhibited the same blood ionized Ca concentration and urinary Ca excretion.…”
Section: Figurementioning
confidence: 67%
“…To circumvent these drawbacks, researchers have bred Casr -/-mice with mice lacking parathyroid glands (7) or unable to synthesize PTH (8). In studies in the latter model, it was proposed that extraparathyroid CaSR was useful for narrowing the variability of blood and urine Ca (8) and dampening the calcemic response to exogenous PTH administration, high-Ca diet, or calcitriol injections (9,10). However, these studies did not aim at providing direct evidence that extraparathyroid Ca is important in determining the value of steady-state blood Ca concentration when PTH is either absent or invariant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out in proximal tubule-derived cell lines also suggest that 1␣-hydroxylase activity is inhibited in the presence of high Ca 2ϩ (97). Recent studies carried out with a murine model in which the full-length CaSR has been ablated (and that expresses an exon 5-less splice variant, therefore representing a "hypomorph" in some tissues) have shown that CaSR dampens the response to 1,25(OH) 2 D 3 independently of PTH actions (39). Thus CaSR exerts a tight control on circulating 1,25(OH) 2 D 3 both at the level of its synthesis (in the proximal tubule) and in modulating its effects (specifically, on calcium reabsorption by the distal tubule, see below).…”
Section: Casr and The Kidneymentioning
confidence: 99%
“…17 In a study carried out with a murine model in which the full-length CaSR has been ablated have shown that CaSR diminishes the response to 1,25(OH) 2 D 3 independently of PTH actions. 18 Thus CaSR exerts a tight control on circulating 1,25(OH) 2 D 3 both at the level of its synthesis (in the proximal tubule) and in modulating its effects. Conversely, 1,25(OH) 2 D 3 , 19 PTH, and dietary phosphate modulate both CaSR gene and protein expression in the proximal tubule, 20 suggesting the existence of a local feedback loop for the regulation of Ca 2+ and P i excretion independently of systemic changes in calciotropic hormones.…”
Section: Casr In Proximal Convoluted Tubulementioning
confidence: 99%